2017
DOI: 10.3389/fpls.2017.01508
|View full text |Cite
|
Sign up to set email alerts
|

Histological and Transcriptomic Analysis during Bulbil Formation in Lilium lancifolium

Abstract: Aerial bulbils are an important propagative organ, playing an important role in population expansion. However, the detailed gene regulatory patterns and molecular mechanism underlying bulbil formation remain unclear. Triploid Lilium lancifolium, which develops many aerial bulbils on the leaf axils of middle-upper stem, is a useful species for investigating bulbil formation. To investigate the mechanism of bulbil formation in triploid L. lancifolium, we performed histological and transcriptomic analyses using s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
75
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(77 citation statements)
references
References 61 publications
2
75
0
Order By: Relevance
“…7). GH3 genes (and especially, GH3.1 (Uni_24954)), encoding IAA-amido synthetase, which conjugates IAA to amino acids, thus reducing the IAA concentration [25], was downregulated throughout bulblet formation.…”
Section: Iaamentioning
confidence: 99%
“…7). GH3 genes (and especially, GH3.1 (Uni_24954)), encoding IAA-amido synthetase, which conjugates IAA to amino acids, thus reducing the IAA concentration [25], was downregulated throughout bulblet formation.…”
Section: Iaamentioning
confidence: 99%
“…Histological and transcriptomic analysis showed that starch synthesis and accumulation was vital to bulblet emergence and development in triploid Lilium lancifolium. [12,13] Zhang et al [14] reported that the starch content of interior scales were higher than that of exterior scales. Starches from different tissue parts differed in colors, sizes, structure, morphology, and texture characteristics, which could affect the functional properties and their suitability for different industrial applications.…”
Section: Introductionmentioning
confidence: 99%
“…Its structural and functional properties have been studied by some previous reports [ 15 , 16 , 17 , 18 ]. The bulbil, also known as Shanyaodou (in Chinese), is an aerial tuber of Chinese yam, which is generated from leaf axil [ 2 , 19 ]. The bulbil can be released from the parent plant and grow independently into a new plant, making it an important propagation organ [ 13 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The bulbil, also known as Shanyaodou (in Chinese), is an aerial tuber of Chinese yam, which is generated from leaf axil [ 2 , 19 ]. The bulbil can be released from the parent plant and grow independently into a new plant, making it an important propagation organ [ 13 , 19 ]. The bulbil of Chinese yam has been used as an important food in people’s everyday life and as an important ingredient in livestock feed.…”
Section: Introductionmentioning
confidence: 99%